GEOCHEMISTRY OF BIOMICROELEMENTS IN IRRIGATED SOILS (Scientific journal of the Fergana State University, 2025)
The article presents the chemical elemental composition of irrigated soils formed in the Fergana region, developed Clark concentrations and geochemical spectra of biomicroelements in these soils. It was also established that the clarke concentrations of Mo and Zn in the horizons of irrigated soils accumulate in comparison with the lithospheric clarke, and the highest values correspond to the arable horizons of soils.